A computational fluid dynamics investigation of a novel flooded-bed dust scrubber with vibrating mesh - Lu, Zhaokuan; Rath, Aishwarya; Amini, Seyed Hassan; Noble, Aaron; Shahab, Shima (International journal of mining science and technology, 2022)
This work proposes a vibrating mesh screen as an alternative to the static mesh screen currently used in conventional flooded-bed dust scrubbers for removing airborne coal mine dust in the continuous mining environment. Fundamental assessments suggest that a vibrating screen may improve the dust collection efficiency of scrubber systems and mitigate the clogging issues associated with the conventional design. To evaluate this hypothesis, computational fluid dynamics (CFD) simulations were carried out to assess the effects of vibration conditions (i.e., frequency and amplitude) on the dust particle-mesh interaction and mesh wetting conditions, which are the two decisive factors in determining the dust collection efficiency. The results suggest that the vibrating mesh screen can enhance dust particle collision opportunities on the mesh and increase mesh wetted area as compared to the static mesh screen. The effects of mesh screen aperture, coal dust concentration, and spray nozzle flow rate on the performance of the vibrating mesh are also evaluated. Finally, a simplified three-phase flow simulation including airflow, dust particles, and water droplet spray is performed, and the results reflect a significant improvement of dust collection efficiency in the liquid-coated vibrating mesh screen.